Psychotic episode in an 11-year-old adolescent: a case report - Maluenda Toro, Sebasti´án (2025)
Psychosis is a clinical condition whose onset takes usually place at an early age and affects thoroughly its victim’s functioning, generating a serious distortion in the overall functioning of the patient. Childhood psychosis is considered a prodromal phase, characterized by active attenuated symptoms which affect the normal development of the patients. The pharmacological treatment suggested for this type of psychopathology is mainly based on the use of second-generation (atypical) antipsychotics, in addition to psychological treatment to the patient and the family network. The clinical case of an 11-year-old patient who presents psychotic symptoms with concomitant suicidal behavior is described and discussed. An initial evaluation is carried out to establish an adequate pharmacological management.